International journal of synthetic emotions - IGI eBooks; IGI Global; Information Resources Management Association (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pa., 17033, USA), 2010)
"The International Journal of Synthetic Emotions (IJSE) covers the main issues relevant to the generation, expression, and use of synthetic emotions in agents, robots, systems, and devices. Providing unique, interdisciplinary research from across the globe, this journal covers a wide range of topics such as emotion recognition, sociable robotics, and emotion-based control systems useful to field practitioners, researchers, and academicians."--Provided by publisher.
"An official publication of Information Resources Management Association."
Also available in print.
Mode of access: World Wide Web.
Description based on: Vol. 1, issue 1 (2010); title from title screen (IGI Global, viewed Oct. 5, 2010).
Latest issue consulted: Vol. 1, issue 2 (2010).
Keywords: Emotions -- Social aspects -- Periodicals; Artificial intelligence -- Periodicals; Robots -- Periodicals; Affective computing; Cognition for ambient intelligence; Cognitive science; Diffusive emotional controls; Electronic art approaches to emotions; Emotional architectures; Emotional computing; Emotional design; Emotional interfaces; Emotional languages programming; Emotion-based control systems; Emotions recognition; Engineering approaches to emotions; Evolutionary approaches to the mind; Feeling or showing emotion differences; Grounding emotions in adaptive systems; Humanoid robotics; Language and emotions; Modeling artificial emotions; Neuroethics; Online emotional avatars; Sociable robotics; Synthetic emotions (SE) in agents, robots, systems, and devices; Theories of emotions; Warm and fuzzy logic for building artificial emotions; Electronic books